The effects of empathy by caregivers on healthcare service satisfaction - Wang, Xiaoyi; Wang, Ruining; Sheng, Feng; Chen, Leyi (Frontiers in Psychology, 2022)
Healthcare service satisfaction focuses not only on the patients but also on the caregivers’ perspectives. This study explored how caregivers’ empathy toward patients affects their satisfaction with healthcare services through an electroencephalography (EEG) experiment. EEG mu rhythm was used as the neural indicator to reflect empathy. The results showed that empathy reduces caregivers’ evaluation of healthcare service satisfaction because they share suffering with the patients. However, implementing physician–patient communication through a process-based informed consent (IC), compared to an event-based IC, can effectively alleviate such adverse effects.